Pursuing epistemological plurality in South Africa's Eco-Schools: Discursive rules for knowledge legitimation - Lisa Ryan; Jo-Anne Ferreira (Environmental Association of Southern Africa, 2019)
Efforts to re-appropriate indigenous knowledges reveal a discursive friction experienced by Eco-School support workers in South Africa as they attempt to build an epistemologically pluralistic curriculum. This paper outlines the strategies that South African Eco-School support workers and teachers employ in negotiating this friction and highlights the discursive rules that govern what constitutes legitimate knowledge in the South African Eco-School. The unintended consequences of these strategies that may affect the representation of indigenous peoples is also discussed.